Recent Advances in the Cellular and Molecular Mechanisms of Hypothalamic Neuronal Glucose Detection - Fioramonti, Xavier; Chrétien, Chloé; Leloup, Corinne; Pénicaud, Luc (Frontiers in Physiology, 2017)
The hypothalamus and brainstem have been recognized for decades as the major brain centers for the control of energy homeostasis. These areas contain specialized neurons able to detect changes in nutrients level. Among them, glucose-sensing neurons use glucose as a signaling molecule in addition to its fueling role. In this review we will describe the different sub-populations of glucose-sensing neurons present in the hypothalamus and highlight their nature in term of neurotransmitter/neuropeptide. This review will particularly discuss whether pro-opiomelanocortin (POMC) neurons from the arcuate nucleus are directly glucose-sensing? In addition, recent observations in glucose-sensing suggest a subtle system, with different mechanisms involved in the detection of changes in glucose level and their involvement in specific physiological function. Several data point out the critical role of reactive oxygen species (ROS) and mitochondria dynamics in the detection of increased glucose. This review will also highlight that ATP-dependent potassium (KATP) channels are not the only channels mediating glucose-sensing and discuss the new role of transient receptor potential canonical channels (TRPC). We will discuss the recent advances in the determination of glucose-sensing machinery and highlight potential line of research needed to further understand the regulation of brain glucose detection.